PENGARUH KOMUNIKASI DAN IKLIM ORGANISASI TERHADAP KEDISIPLINAN KERJA KARYAWAN PT. SAWIT RIAU MAKMUR MEDAN - Wily Julitawaty; Joceline Giovanna Angel; Nur Subiantoro (JURNAL BISNIS KOLEGA, 2021)
Abstract. The method used in this research is a survey approach. Both population and sample in this research are all of PT. Sawit Riau Makmur Medan’s employees; with the total of 32 employees. The methods of collecting data are interview, documentary studies, observation, and questionnaire distribution. The variables are measured with Likert scale. The model of data analysis used to answer the hypothesis is multiple regression analysis.The research results show that in terms of partial influence, both communication and organizational climate affect but not significantly to the work discipline. And in terms of stimultant influence, communication and organizational climate affect but not significantly to the work discipline. Keywords: Communication, Organizational Climate, Work Discipline, Employe